You can take them with you - Muendler, Marc-Andreas,Rauch, James E.,Koyama, Sérgio Mikio (CESifo, 2024)
New firms do not yet have employees who can aid recruiting by referrals, but entrepreneurs can recruit workers they know to their startups—in effect making their own referrals. We consider new firms in Brazil’s formal sector founded between 2002 and 2014, for which at least one founding owner can be traced to previous formal employment. We find that 35.1 percent of new firms with at least five employees hire one or more coworkers from a founding owner’s last employer in their first year of operation, and that 9.2 percent of first-year hires at new firms were coworkers at a founding owner’s last employer. The former coworkers most likely to join a founding owner’s new firm are those who, at their last employer, worked in the same plant as a founding owner, had long overlap with a founding owner, were classified in the same industry or occupation as a founding owner, and were hired at roughly the same time as a founding owner. Controlling for observable human capital and new firm fixed effects, former coworkers earn eight percent higher initial wages at new firms and are six percentage points less likely to separate before a new firm’s second year of operation. We find that the coworker wage premium diminishes with tenure by 0.5 percentage points per year and the coworker separation premium diminishes with tenure by 2.0 percentage points per year.
https://www.cesifo.org/en/publications/2024/working-paper/you-can-take-them-you-recruiting-coworkers-ones-own-new-firm
Keywords: Graue Literatur; job referrals; business formation; entrepreneurship; employee spinoffs; firm performance